Parkinson’s Disease Dementia and Dementia with Lewy Bodies Have Similar Neuropsychological Profiles - Aldridge, Georgina M.; Birnschein, Allison; Denburg, Natalie L.; Narayanan, Nandakumar S. (Frontiers in Neurology, 2018)
Parkinson’s disease dementia (PDD) and dementia with Lewy bodies (DLB) are common causes of dementia worldwide.  Although considered separate entities based on the relative temporal onset of motor symptoms versus diagnosis of dementia, it is unknown if these diseases truly have distinct cognitive profiles.  We hypothesized that patients divided into PDD and DLB categories strictly by temporal criteria would have different neuropsychological profiles. We investigated this question via neuropsychological testing of PDD and DLB patients at the University of Iowa. We performed retrospective chart analysis and review of neuropsychological testing of clinically diagnosed patients with PDD or DLB, who had presented to University of Iowa’s dementia and movement disorder clinics. Forty-seven patients diagnosed by the treating neurologist as PDD or DLB were included. Neuropsychological performance was compared between groups, and as a function of the relative timing of the motor diagnosis vs. diagnosis of dementia. We found that both PDD and DLB patients showed severe deficits in executive function, visual-spatial processing and verbal learning. However, we found no significant differences in neuropsychological performance between groups, and neuropsychological performance could not reliably account for the relative timing of motor diagnosis versus diagnosis of dementia. Our data support the idea that DLB and PDD are on a neuropsychological spectrum.